Diagnóstico da situação da teníase e da cisticercose bovina no município de Salinas/MG, 2010 - Fernanda do Carmo Magalhaes (2011)
The objective of this study was to evaluate the health situation of the taeniasis cysticercosis complex in the city of Salinas-MG, by estimating the prevalence of bovine cysticercosis and human taeniasis in rural properties and determine the health conditions and socio-economic ofeach property. We conducted a cross-sectional study involving properties located in the rural area, where 355 samples were collected from bovine blood, stool samples of all residents of farms and application of a questionnaire. Moreover, it was an epidemiological survey of taeniasis cases diagnosed in laboratories accredited by the Municipal Department for the period 2007-2010. The diagnostic parasitology was Method of Hoffman and serological diagnosis of cysticercosis animal was performed by screening by ELISA and suspected cases were subjectedto Immunoblot for confirmation. The survey revealed a true prevalence of bovine cysticercosis of 4.70% (IC 95%= 2.50 to 6.90). The prevalence of taeniasis found in the last four years in the city of Salinas / MG was 0.29% in 2007, 0.36% in 2008, 0.24% in 2009 and 0.24% until the month october 2010. Entamoeba histolytica (33.33%) and Entamoeba coli (30.95%) were parasites of high incidence in the rural municipality of Salinas. The families sampled in this study, owners of low income, highlighted by the use of untreated water for human consumption, supplying untreated water to the animals, breeding extensively and with little use oftechnological resources. Furthermore, were found favorable characteristics for maintenance of the taeniasis cysticercosis complex as open sewers, slaughter without sanitary inspection, and consumption of undercooked meat. But only the heat treatment of beef showed a significant difference in the simulation analysis of association between potential risk factors for transmission of the taeniasis cysticercosis complex.